'Hooray! Hooray! the End of the World has been Postponed!' Politics of Peace in the Adventures of Tintin?. (October 2014) - Rösch, Felix
Tintin is a cultural icon whose popularity has led to critical assessments accusing the comic of perpetuating orientalist and racist images. This article presents a different reading of Tintin by asking a more fundamental question: what understanding of the political is manifested in Tintin's Adventures? I argue that Tintin creates a political sphere that fosters an image of peace which does not eradicate conflicts, but facilitates them. Bildung, spatio-temporal conditionality of knowledge, spheres of elasticity, and power ensure that they do not turn into violence. All these are characteristics of the comic and create a powerful visualisation of the human condition of politics.